Is the concept of type D personality a component of personalized medicine or a prognostic factor in the treatment of cardiovascular diseases? - A. N. Sumin; A. V. Shcheglova (Российский кардиологический журнал, 2020)
The study of a patient's personal traits is reasonable and relevant in the implementation of personalized medicine in cardiology. The use of type D personality concept seems suitable for such aims. Type D personality refers to chronic psychosocial risk factors, which associated with a decrease in the quality of life, and is recommended for screening. Additional analysis showed the heterogeneity of type D effect on prognosis depending on the stage of disease (coronary artery disease or heart failure), age, and endpoints used. In addition, ethnic, geographic and socio-economic factors, differences in the mentality can also affect the predictive value of type D personality. Possible mechanisms of its influence on the prognosis are maladaptive response to stress, as well as the behavioral characteristics of such patients. In assessing the type D effect, it has recently been proposed to use additional calculations with an estimate of the addictive and synergistic effects. In clinical practice and screening studies, conventional assessment of type D personality using the DS-14 questionnaire seems reasonable. Until now, the question of influencing persons with type D personality remains unstudied. The following treatment strategies look promising: change of excessive responses to stress; the influence on inadequate stress coping strategies. The ultimate goal of such interventions should be not only to improve the psychological functioning of patients, but also to slow down the progression of the physical illness and improve the prognosis.